Migration and education on social media: what migrants discuss about education in Facebook groups - Dedecek Gertz, Helena (Frontiers in Sociology, 2023)
Drawing from a networked perspective of migration and from the concept of “transnational education,” this paper investigates the education-related topics discussed in Facebook groups among Brazilian migrants in Germany. The paper examines the “latent ties” activated in migrant Facebook groups as part of networks that can be used to collect information about migratory pathways involving educational opportunities. A qualitative content analysis was conducted with 2.297 posts retrieved from six Facebook groups divided into location, vocational education and training (VET), and professional groups. The outcomes point out that there is a demand for transnational education beyond university degrees. Additionally, the paper highlights that latent ties can be used to collect and cross-check information in migratory contexts involving education.